An Evolutionary Metaheuristic for the 2D Guillotine Cut Problem - José Ignacio Peláez; A. H. Yánez; Eduardo A. Santos; L. M. Moncayo (Journal of Systemics, Cybernetics and Informatics, 2016)

(untitled)
The two-dimension guillotine cut is actually one of the most interesting problems in modern industries like metallurgic, textile, wooden... in which it's needed to cut sheets in pieces with an associated dimensions and benefits in the way to maximize the final benefit. The purpose of this work is to present an evolutionary metaheuristic for the two-dimension cut problem using guillotine, also it's shown how this approach can be applied to solve these types of problems, it's compared with other exact algorithms and finally it's defined an evolutionary representation which may be used with different metaheuristics.